1992
DOI: 10.1159/000236204
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Properties of Anti-DNA Antibodies in the Sera of Patients with <i>Escherichia col</i><i>i</i> Bacteremia

Abstract: To assess the role of infection in anti-DNA antibody production, the DNA-binding activity of sera from patients with Escherichia coli bacteremia was analyzed. Among 8 patients with bacteremia documented by blood culture, 5 demonstrated increased levels of antibodies to single-stranded DNA from E. coli as measured by enzyme-linked immunosorbent assay. Sera from these patients also reacted with single-stranded DNA from other bacterial and mammalian species as well as certain synthetic polynucleotides including p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Inspired by the Pisetsky observations, we observed a similar dichotomous response when we immunized mice with linearized polyomavirus dsDNA in complex with a carrier-protein. Normal mice produced antibodies to viral dsDNA ( 158 ), while applying the same immunization regime on young lupus-prone mice, they produced antibodies to both viral and mammalian dsDNA ( 159 , 160 ); i.e., results that were in agreement with the data published by Pisetsky et al ( 83 , 135 , 161 ).…”
Section: Virus Infectious-related Immune Responses To Nucleic Acids—tsupporting
confidence: 84%
“…Inspired by the Pisetsky observations, we observed a similar dichotomous response when we immunized mice with linearized polyomavirus dsDNA in complex with a carrier-protein. Normal mice produced antibodies to viral dsDNA ( 158 ), while applying the same immunization regime on young lupus-prone mice, they produced antibodies to both viral and mammalian dsDNA ( 159 , 160 ); i.e., results that were in agreement with the data published by Pisetsky et al ( 83 , 135 , 161 ).…”
Section: Virus Infectious-related Immune Responses To Nucleic Acids—tsupporting
confidence: 84%
“…These antibodies thus resemble antibodies to bacterial DNA that occur in the sera of NHS. These NHS antibodies bind selectively to DNA from certain bacteria and appear to target nonconserved sites occurring on DNA in a species-specific manner (17)(18)(19)(20). In the current experiments, with a CpG ODN as adjuvant, the antibodies from normal mice immunized with either EC or CT nDNA as immunogens bound cross-reactively with both ssDNA antigens, suggesting induction of certain types of autoantibodies.…”
Section: Discussionmentioning
confidence: 63%
“…Since sera of normal human subjects (NHS) have appreciable antibody titers to DNA from certain bacterial species, bacterial DNA may nevertheless be effective immunogens in vivo (17)(18)(19)(20). During the setting of colonization or infection, other bacterial antigens (e.g., endotoxin) may augment responses by serving as "danger" molecules and causing nonspecific immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors denied the existence of flare-ups during pregnancy [6,7], whereas others suggested a high rate of flare-ups in pregnancy and puerperium [3,4,8]. The contribution of systemic infection, especially bacterial infection caused by E. coli, in autoimmune diseases has been previously reported [9,10]. In addition, the characteristics at the time of flare-ups in these pregnant patients were similar to those of non-pregnant patients.…”
Section: Discussionmentioning
confidence: 91%